Manajemen Sekolah Adiwiyata (Green School) - Asep Priatna (Lembaga Layanan Pendidikan Tinggi Wilayah IV, 2020)
The issue of environmental pollution has come to the attention of the world community and has become a strategic issue in sustainable development, so it needs to have the support of all parties, including the government, the private sector and educational institutions. Integrated Junior High School Lampang, Subang Regency West Java Indonesia has been implementing the green school program since 2008 and in 2019 it was entrusted by the West Java Education Office to be proposed as a national level green school program. Some achievements as a green school implementing school are private schools that have obtained